Malawi : Joint Staff Assessment of the Poverty Reduction Strategy Paper Progress Report. (IMF Staff Country Reports; Country Report ;, 2003)
This joint staff assessment evaluates the strengths and weaknesses of Malawi's poverty reduction strategy (MPRS), and considers whether the PRSP provides a sound basis for concessional assistance from the World Bank and IMF, as well as for debt relief under the Enhanced Heavily Indebted Poor Countries (HIPC) Debt Initiative. The annual review of the MPRS highlighted the reduced allocation of budgetary resources to pro-poor activities and the slow progress made in implementing structural and sectoral policy measures, and assesses that the implementation of the MPRSP has been unsatisfactory.